Insulation failure evaluation of SF6 circuit breaker relay coil based on high-frequency equivalent model. Issue 1 (1st April 2022) - Qin, Jian; Peng, Yanjun; Wang, Lu; Pan, Ningbo; Chen, Jianxi; Huang, Yongqiang; Jiang, Wei
Abstract: In order to evaluate the insulation failure of SF6 circuit breaker relay coil, the finite element model of the relay coil was established, and the capacitance inductance matrix was calculated by simulation calculation, and the high-frequency equivalent circuit model of the coil was established. Inject low-voltage square wave pulse signal at the input end of the circuit, and the response curve is detected at the end of the circuit, and the characteristic curve is obtained by combining the response curve under the condition of inter-turn short circuit fault and no fault. The wavelet packet - energy spectrum analysis shows that the energy proportion of each frequency band of the characteristic curve changes when the short-circuit position between turns is different. Taking energy spectrum as input and combining with extreme learning machine to locate inter-turn short circuit fault, the simulation sample analysis shows that the correct rate of fault location is 93.3%.